Modified Kudryashov method and its applications to the (2+1)-dimensional cubic Klein-Gordon and (3+1)- dimensional Zakharov-Kuznetsov equations - M. Abdul Al Woadud, K.; Jahirul Islam, Md.; Rahman Khan, Aminur (International Journal of Physical Research, 2022)
The exact solutions of nonlinear evolution equations (NLEEs) play a vital role to reveal the central mechanism of complex physical phe-nomenon. More precisely, in this paper, we acquired new exact solutions to the (2+1)-dimensional cubic Kleinâ€“Gordon (cKG) and (3+1)-dimensional Zakharovâ€“Kuznetsov (ZK) equations by using the modified Kudraysov method. As results, a portion of the new accurate voyaging wave answers for the situations above is officially delivered. All arrangements are plotted in the perspective on three-dimensional (3D) and two-dimensional (2D) line shape through the MATLAB programming for exploring the genuine meaning of the concentrated on conditions. The periodic type of solution is created using a modified Kudryashov approach, which is distinct from the other methods investigated.Â Â